Cost-effectiveness analysis of abobotulinumtoxinA for the treatment of cervical dystonia in the United Kingdom - Muthukumar M; Desai K; Abogunrin S; Harrower T; Gabriel S; Dinet J (Dove Medical Press, 2017)
Madhusubramanian Muthukumar,1 Kamal Desai,1 Seye Abogunrin,2 Timothy Harrower,3 Sylvie Gabriel,4 Jerome Dinet5 1Modelling and Simulation, 2Meta Research, Evidera, London, 3Royal Devon and Exeter NHS Foundation Trust, Exeter, UK; 4Global Market Access and Pricing, 5Health Economics and Outcomes Research (Global), Ipsen Pharma, Boulogne-Billancourt, France Background: Cervical dystonia (CD) involves painful involuntary contraction of the neck and shoulder muscles and abnormal posture in middle-aged adults. Botulinum neurotoxin type A (BoNT-A) is effective in treating CD but little is known about its associated cost-effectiveness.Objective: To evaluate the cost-effectiveness of abobotulinumtoxinA for treating CD from the UK payer perspective.Methods: A Markov model was developed to evaluate the cost-effectiveness of abobotulinumtoxinA versus best supportive care (BSC) in CD, with a lifetime horizon and health states for response, nonresponse, secondary nonresponse, and BSC in patients with CD (mean age: 53 years; 37% male). Clinical improvement measured using Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) was mapped to utility using data from a randomized trial of abobotulinumtoxinA. Health care resource use, costs, and other inputs were from the British National Formulary, Personal Social Services Research Unit, published literature, or expert opinion. Costs and outcomes were discounted at 3.5% per annum.Results: In the base case, the incremental lifetime quality-adjusted life-years (QALYs) gained from abobotulinumtoxinA arm versus BSC was 0.253 per patient, whereas the incremental cost was £7,160, leading to an incremental cost-effectiveness ratio (ICER) of £30,468 per QALY. One-way sensitivity analyses showed that these results were sensitive to the proportion of responders to abobotulinumtoxinA at first injection, duration between injections, the number of reinjections allowed among primary nonresponders, and any difference in baseline TWSTRS value between the BSC and abobotulinumtoxinA arms. Probabilistic sensitivity analysis showed that abobotulinumtoxinA was cost-effective 46% and 49% of times at thresholds of £20,000 and £30,000 per QALY, respectively. Scenarios are considered including vial-sharing, productivity losses, secondary response/nonresponse at subsequent injections, 5-year time horizon, and alternative reinjection intervals for BoNT-As produced ICERs ranging from cost-saving to £40,777 per QALY, versus BSC.Conclusion: AbobotulinumtoxinA was found to be cost-effective in treating adults with CD, at acceptable willingness-to-pay thresholds in the UK. Keywords: cost-effectiveness analysis, cervical dystonia, botulinum neurotoxin type A, abobotulinumtoxinA